Binary Opposition Under Monitoring at a Wedding Ceremony in Gunung Karto Village, Tanjung Sakti Pumi District, Lahat Regency, South Sumatra Province - Avrilia; Suharti; Oktayanty, Yetty (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This research is entitled Binary Opposition in Observations at Wedding Ceremonies in Gunung Karto Village, Tanjung Sakti Pumi District, Lahat Regency, South Sumatra Province. The aim of this research is to describe the processes involved in monitoring, and the meaning contained in the monitoring tradition. The theory used in this research is Levi Strauss's binary opposition. The method used in this research is a qualitative method. Data collection was carried out using observation, interviews and documentation methods. The data analysis technique carried out in this research uses steps including collecting data, reducing data, presenting data and drawing conclusions. The results of this research show that the monitoring tradition is a customary law that has been implemented for generations until now. The monitoring tradition has three processions, namely bubus, akad, and monitoring. In the tradition, monitoring has the meaning of understanding the family tree and togetherness. Furthermore, in one of the traditional processes of monitoring, it is considered mutual opposition between the groom and the bride. This process is monitoring, where when the woman's family carries out the contract, it is the man's family who monitors it and vice versa.